Physical science teachers' responses to curriculum challenges in South Africa - pedagogical content knowledge focused case studies - Nakedi, Emily Mmamontle (My University, 2014)
A critical question which continues to dominate debates in the field of science education is why curriculum reform innovations do not effect change and raise the quality of inputs in most teachers’ classroom practices. In this study, I worked with two teams of teachers in two different settings constituting two case studies to try to understand how teachers handle change in complex situations, with the aim of identifying appropriate strategies which can be effective in responding to their immediate professional needs in the classroom. A multiple case study approach was adopted, with the first case referred to as a minor case study and the second as a major case study. Within the major case study, the four participating teachers also constituted sub-cases on their own. Data were analysed using pedagogical content knowledge (PCK) as a conceptual framework and interpretive analysis grounded in hermeneutic phenomenology to show how the teachers’ knowledge base for teaching was shifting as they engaged individually and collectively on systematic-experiential cycles of reflecting on and in actions of planning for and teaching a new topic in their classrooms, as well as how their beliefs about learners and learning interfaced with their classroom practices. Even though this study targeted the teachers’ intrinsic resources and how these can be developed and mobilized to enhance the teachers’ efforts to enact change, contextual issues emerged very strongly in the minor case study. Hence through the minor case study, I show why stabilizing the dynamics in the wider school context, should take precedence over site-based subject-specific professional development. I show how factors in the enveloping school environment can either enhance or undermine any efforts aimed at effecting changes in the subject-specific teacher classroom practices, and why school collegiality is a prerequisite. With the major case study, I supervised the four participating teachers who undertook self- studies to learn how to teach a new topic in the science curriculum, as part of their BSc honours projects. Within this project, they explored the use of pedagogic research-based strategies and tools such as the concept representation (CoRe), structured, systematic journaling cycle and the 5Es constructivist lesson sequencing strategy to address chemical systems topics in grades 10, 11 and 12. I showed how the four teachers’ PCK, their notions, conceptions, perspectives and knowledge about the learning and teaching of science, planning for its teaching, the act of teaching it, and the related meta-cognition affected, as they engaged with the process. One of the evolving contributions of this thesis which served as a framework to guide the study, is the learning for teaching through participation (LTtP) model. The LTtP offers a useful framework that provides a mechanism through which the PCK of science teachers can be developed. I used this model to map three of the teachers’ individual growth patterns. It emerged that teacher growth patterns are idiosyncratic, topic-specific and shifting because teacher change is bound to time, place and person. This finding demonstrated the capacity of LTtP to serve as a useful tool for understanding and interpreting teacher learning in innovation environments. Methodologically I show that even though the potential of the CoRe as a research, planning, meta-cognition developing tool was not fully explored, it served as a great tool to initiate and support the development of the participating teachers’ topic specific subject matter knowledge (SMK), as well as related meta-cognitive skills. Ingenuity and authenticity of PCK-focused self-studies, in capturing and addressing curriculum innovation challenges, was demonstrated by the varied levels and complexity of cognitive, meta-cognitive, affective as well as pedagogic learning the teachers were able to amass within the limited period. KEY WORDS Teacher learning environments, science learning and teaching, curriculum innovation, pedagogic content knowledge and metacognition